Model Cooperative Learning Berbasis Numerasi di Sekolah Setia Asih 01 Bekasi - Manurung, Alberth; Halim, Abdul; Muhammad Nur, Syurya (Journal of Classroom Action Research, 2025)
Numeracy-based Cooperative Learning is the basis for students in solving mathematical problems. Based on the results of initial observations conducted on students at SDN Setia Asih 01 Bekasi Regency, it was revealed that working on math problems is a problem, therefore a numeracy-based Cooperative Learning learning model is needed. Thus, the ability of numeracy-based Cooperative Learning can be used as an alternative solution to educational problems. This study aims to analyze the ability of numeracy-based Cooperative Learning of grade VI students through numeracy-based Cooperative Learning for students in elementary schools. The type of research used is The method used in this study is a mixed method of quantitative and qualitative methodology, with the design used in this study is The exploratory sequential design. Respondents in this study were 32 grade VI students. Data analysis in this study used descriptive and inferential statistics in the form of simple linear regression analysis. Based on the results of the study, it shows that the ability of numeracy-based Cooperative Learning can significantly improve their mathematics learning. Students' numeracy-based Cooperative Learning abilities are influenced by Cooperative Learning by 44.2%. Meanwhile, 55.8% was influenced by other factors outside of student numeracy-based cooperative learning.